Resistance to Cotrimoxazole and Other Antimicrobials among Isolates from HIV/AIDS and Non-HIV/AIDS Patients at Bugando Medical Centre, Mwanza, Tanzania - Karol J. Marwa; Martha F. Mushi; Eveline Konje; Paul E. Alele; Jeremiah Kidola; Mariam M. Mirambo (AIDS Research and Treatment)
Bacterial resistance has increased in the AIDS era and is attributed to the widespread use of cotrimoxazole prophylaxis against opportunistic infections in HIV/AIDS patients. In Tanzania, cotrimoxazole prophylaxis has been used for more than ten years. Little is known, however, about its impact on the spread of antibiotic resistance in HIV positive patients. This cross-sectional study was done to compare magnitude of bacterial resistance to cotrimoxazole and other antimicrobials among isolates from HIV infected patients on cotrimoxazole prophylaxis and those not on prophylaxis and non-HIV patients attending Bugando Medical Centre (BMC). Susceptibility testing on obtained urine and swab specimens followed Clinical Laboratory Standard Institute, 2010, Guidelines. Of 945 samples collected, 155 had positive bacterial growth after 24 hours of incubation. Of the positive samples (72), 46.4% were from HIV positive patients. The common isolates were E. coli 41.3% (64/155), Klebsiella pneumoniae 17.5% (27/155), and Staphylococcus aureus 16.1% (25/155). Overall, bacterial resistance to cotrimoxazole was 118 (76.1%); among isolates from HIV patients bacterial resistance was 54 (75%), and for isolates from HIV patients on prophylaxis bacterial resistance was 36 (81.3%). HIV seropositivity and cotrimoxazole prophylaxis are not associated with antibiotic resistance observed in bacteria infecting patients attending BMC, Mwanza, Tanzania.